Comparação de dois conversores Boost, para aplicação em carregadores de baterias de um sistema fotovoltaico autônomo, aplicando princípios da engenharia de valor - Lima, André dos Santos (2008)
This work presents a comparison between two different boost converters, a three state commuting cell boost and a classical one, used as battery chargers on a stand-alone photovoltaic system. The two converters were built to substitute a battery charger of a UPS system that works with 48 volts from the batteries. This UPS system must be used to supply a residence of the program “Luz para todos” from the Brazilian government. The minimum converter’s output power, in 500 watts, for a consumer of the 30 kWh/month was extracted of the rule number 83 from ANEEL (National electrical energy agency) From the assembled prototypes, experimental results were made in order to choose the best converter topology based on principles of value engineering.